Boom to bust? Implications for the continued rapid growth of the eastern Australian humpback whale population despite recovery. Issue 2 (4th February 2019) - Noad, Michael J.; Kniest, Eric; Dunlop, Rebecca A.
Abstract: Despite heavy overexploitation and near extirpation, some populations of large whales are recovering. Monitoring their recovery has important implications for conservation, management and our understanding of population dynamics and recovery in large mammals. The eastern Australian population of humpback whales was hunted to near‐extirpation by the early 1960s. Despite this, the population started to recover, and structured surveys were initiated in the 1980s. These surveys comprise one of the longest and most consistent series of surveys of a population of whales in the world. Collectively, they have demonstrated a rapid recovery of the population with a long‐term average rate of increase of 10.9% per annum. Here, we present the results of the last three surveys, conducted in 2007, 2010 and 2015. The 2015 survey shows that the population is essentially recovered, with abundance estimated at 24, 545 whales (95% confidence interval 21, 631–27, 851), and yet continues to grow at a rapid rate. Modeling the rate of growth and abundance suggests that either the whales are heading for a higher than expected abundance of at least 40, 000 whales or that an irruption may occur with models suggesting a peak in whale abundance in 2021–2026. Understanding the possible future scenarios of this population is critical to its management. This situation also presents a rare opportunity to study in detail the growth of a well‐defined population of large mammal as it recovers from severe depletion.